Exploring ecomorphological patterns and the evolution of shape in Stomiiformes (Actinopterygii: Teleostei): a study of deep-sea fish adaptations - Gomes, Amanda Alves (2023)
Stomiiformes is a monophyletic and diverse group of mesopelagic and bathypelagic fishes that includes 457 valid species classified in 52 genera and five families, including bristlemouths, lightfishes, hatchetfishes, and dragonfishes and their allies. The objective of this study is to investigate the patterns of body shape and skull shape evolution among the stomiiforms using two- and three-dimensional geometric morphometrics in an ecological and phylogenetic context. For the body-shape investigation, a total of 473 specimens from 55 different species were photographed, then, fourteen homologous landmarks and 50 semilandmarks were defined on the digital images. For the skull-shape investigation, a total of 29 stomiiforms skull were scanned using a micro-CT scan tomograph, then 33 homologous landmarks were defined on the three-dimensional reconstructions. Morphometric data was submitted to principal component analysis (PCA), and to comparative methods (morphological disparity and Procrustes ANOVA) analysis to visualize differences in variance among stomiiform clades, dietary classes, depth, skull proportions and tooth traits, then, linked with a recent phylogeny and tested for phylogenetic signal. Overall, all stomiiforms clades vary in terms of skull and body shape, but morphological disparity was higher in dragonfishes (Stomiidae) and hatchetfishes (Sternoptychidae). Regarding body-shape, the main axis of total variation describes a transition from species with a midbody dorsal fin, long anal fin, and body fusiform or deep to species with the dorsal fin positioned more posteriorly on the body and parallel to a short anal fin, in an elongated body. Regarding skull shape, the main axis of total variation describes a transition from a deep skull to an elongated skull, and large jaws. There is a trend towards body elongation in relation to depth distribution, with the meso-bathypelagic species having more elongated bodies than those restricted to the mesopelagic zone. Also, piscivorous and generalist species exhibit higher morphological disparity regarding body-shape when compared to the zooplanktivorous ones. However, when phylogeny is accounted for the body-shape morphological disparity is not significative. In contrast, regarding only the skull, there was no significant correlation between skull shape and ecological traits, with or without the effect of phylogeny. Additionally, there was a significative and strong phylogenetic signal in both skull and body shape among stomiiforms, with closely related taxa tending to cluster together in the phylomorphospace, as a result of the shared evolutionary history, which is often interpreted as evolutionary or phylogenetic conservatism. This is the first study to quantitatively investigate changes in the body and skull shape of stomiiforms. Although stomiiforms have a remarkable morphological disparity in body and skull shapes, the shape evolution within the taxa is explained mostly by the phylogeny of the group, as a result of a shared ancestry pattern. Ecological traits, such as diet, ocean depth, and diel vertical migration are unlikely to play a major role in shaping the morphological evolution of stomiiforms. Another possible hypothesis is that the selected data was not able to detect the significance of ecology in the taxon sampling chosen here.